Nutritional supplements and medications in sport - polypharmacy or real need? - Suzic, J.; Dikic, N.; Radivojevic, N. (Archivos de medicina del deporte, 2008)
Introduction: Expert panel of the Australian Institute of Sport (AIS) categorize nutritional supplements (NS) in four groups: group A - approved NS, group B - NS under consideration, group C - no clear proof of beneficial effects and group D - banned NS. Objectives: The aim of our study was to describe qualitatively and quantitatively dietary supplements and medications used by elite athletes. Methods: We analyzed data collected from Doping Control Forms from national, international competitions and out-of-competition done by Anti-Doping Agency of Serbia from 2005 - 2008. Athletes (n = 618; age 24.2 ± 5.8 yrs; 72% male) competing in various sports were asked about medications and supplements taken within 3 days before doping control. Results: Among reported substances (n = 1535), 68.5% (1052) were NS and 29.6% (455) medications. NS have taken by 58% (2.87 per athlete) and medications by 39% of athletes (1.87 per athlete). Almost 18 % of all users reported use of 6 or more different products and one athlete took 17 different products at the same time. Three most commonly used NS were multivitamins, multi-minerals and amino acids, respectively. In terms of AIS classifi cation, majority of used NS was from group A (59.6%) and from group B, C and D, 4.6%, 35.1%, 0.8%, respectively. Majority of athletes who reported use of medication used NSAID (n = 173, 71.8%; 27.9% of all examined athletes). More than one NSAID was taken by 26% (45) users. In addition, more frequent use of NS among younger athletes was observed (p <0.05). Conclusion: Our study confirmed overuse of supplements and drugs by elite athletes. Fact that large number of athletes used supplements with no evident performance or health benefits, demonstrated the need for specific educational initiatives. Amount, quantity and combination of reported products raised concern about risk of potential side events.